Patient and clinician perspectives on pharmacogenetic testing for antipsychotics - Richards-Brown, Maria; Wei, Yiran; Abidoph, Rosemary; Varney, Lauren; Cotic, Marius; Murtough, Stephen; Panconesi, Daniele; Mills, Daisy; Richards-Belle, Alvin; Saadullah Khani, Noushin; Chipp, Beverley; Bramon, Elvira; et al. (Frontiers in Pharmacology, 2025)
Background/objectivesMedications to treat psychosis (i.e., antipsychotics) have common and sometimes serious adverse drug reactions and can require several trials before finding a suitable drug and dose. To address this, there is increasing focus on personalizing medicine. Pharmacogenetics investigates how genetic variation influences drug metabolism and response, with recent clinical trials suggesting pharmacogenetic testing can improve remission and reduce adverse drug reactions. Therefore, understanding stakeholder perspectives on acceptability is critical.MethodsThis pilot study is part of ‘GEMS’ (Genetics and Environment in Mental Health Study), which investigates pharmacogenetic testing for psychosis. A participant survey, co-created with patients, was completed by 22 patient-participants, and semi-structured interviews were conducted with 11 clinician-participants who had used pharmacogenetic test reports with patients.ResultsBoth patients and clinicians were generally positive about pharmacogenetics, although clinicians saw this as just one component in the multifactorial process of individualized prescribing. Clinicians and patients both suggested a more user-friendly format of the pharmacogenetic report to enhance patient understanding. Some described the reports as promoting more collaborative care, but this was not universal. Clinicians highlighted both retrospective and prospective value in pharmacogenetics providing more certainty through reducing ‘trial-and-error’ prescribing. However, accessibility, understanding, and logistics were identified as potential barriers to implementation.ConclusionAmong patients and clinicians who have experienced pharmacogenetic testing to inform antipsychotic prescribing, acceptability is good. There is potential for pharmacogenetics to enhance personalized prescribing, but barriers to widespread implementation remain.